Population density predicts youth's physical activity changes during Covid-19 – Results from the MoMo study. (July 2021) - Nigg, Carina; Oriwol, Doris; Wunsch, Kathrin; Burchartz, Alexander; Kolb, Simon; Worth, Annette; Woll, Alexander; Niessner, Claudia
Abstract: Children in Germany showed positive physical activity changes during the first Covid-19 lockdown in April 2020, but it is unclear how the changes relate to population density, which we investigated in a longitudinal sample of 1711 youth (4–17 years). For each ten citizens more per km 2, less positive physical activity changes were observed. For example, a child living in an area with 100 citizens/km 2 increased daily life physical activity by 44.50 min/day, whereas a child living in an area with 3000 citizens/km 2 only engaged in an additional 9.70 min/day. Policymakers should ensure that youth in densely populated areas have access to physical activity opportunities during the pandemic. Highlights: Physical activity increased in less densely populated areas during the lockdown. No or little physical activity changes in more densely populated areas. The association was the same for younger and older children. The association was the same for boys and girls.